Host Genetic Background Strongly Affects Pulmonary microRNA Expression before and during Influenza A Virus Infection - Preusse, Matthias; Schughart, Klaus; Pessler, Frank (Frontiers in Immunology, 2017)
Background Expression of host microRNAs (miRNAs) changes markedly during influenza A virus (IAV) infection of natural and adaptive hosts, but their role in genetically determined host susceptibility to IAV infection has not been explored. We, therefore, compared pulmonary miRNA expression during IAV infection in two inbred mouse strains with differential susceptibility to IAV infection. Results miRNA expression profiles were determined in lungs of the more susceptible strain DBA/2J and the less susceptible strain C57BL/6J within 120 h post infection (hpi) with IAV (H1N1) PR8. Even the miRNomes of uninfected lungs differed substantially between the two strains. After a period of relative quiescence, major miRNome reprogramming was detected in both strains by 48 hpi and increased through 120 hpi. Distinct groups of miRNAs regulated by IAV infection could be defined: (1) miRNAs (n = 39) whose expression correlated with hemagglutinin (HA) mRNA expression and represented the general response to IAV infection independent of host genetic background; (2) miRNAs (n = 20) whose expression correlated with HA mRNA expression but differed between the two strains; and (3) remarkably, miR-147-3p, miR-208b-3p, miR-3096a-5p, miR-3069b-3p, and the miR-467 family, whose abundance even in uninfected lungs differentiated nearly perfectly (area under the ROC curve > 0.99) between the two strains throughout the time course, suggesting a particularly strong association with the differential susceptibility of the two mouse strains. Expression of subsets of miRNAs correlated significantly with peripheral blood granulocyte and monocyte numbers, particularly in DBA/2J mice; miR-223-3p, miR-142-3p, and miR-20b-5p correlated most positively with these cell types in both mouse strains. Higher abundance of antiapoptotic (e.g., miR-467 family) and lower abundance of proapoptotic miRNAs (e.g., miR-34 family) and those regulating the PI3K-Akt pathway (e.g., miR-31-5p) were associated with the more susceptible DBA/2J strain. Conclusion Substantial differences in pulmonary miRNA expression between the two differentially susceptible mouse strains were evident even before infection, but evolved further throughout infection and could in part be attributed to differences in peripheral blood leukocyte populations. Thus, pulmonary miRNA expression both before and during IAV infection is in part determined genetically and contributes to susceptibility to IAV infection in this murine host, and likely in humans.